(untitled) (The Research of Medical Science Review, 2025)
Tungiasis is a zoonotic disease caused by female sandflea (Tunga penetrans). The fleas typically inhabit sandy environments, tropical and sub-tropical habitat of world. Main goal of the study was to find out the knowledge, attitude and practices of tungiasis among the population of Lahore. The prevalence of tungiasis and sociodemographic variables were analyzed descriptively. In this study, total 800 people have been questioned about tungiasis from 18 towns. The knowledge about tungiasis were 62.1%. The prevalence of tungiasis were most in animals as compared to human. Mostly the animals affected by tungiasis were cow and buffalo. Attitude of respondents for protection of animals from tungiasis were 59.3%. Several treatments coconut oil, ethanol and glycerine were applied by respondents to cure their animals from tungiasis. Further questionnaire responses indicates that respondent make efforts to the clean place of animals, keep good hygiene, wear shoes, washing hands after dealing with animals for the prevention of tungiasis. There should be awareness campaigns regarding the mode of transmission of tungiasis and its preventative strategies.